1976
DOI: 10.1029/gl003i011p00689
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the charge exchange lifetimes on mirror latitude

Abstract: The dependence of the charge exchange lifetimes on the mirror latitude for ions mirroring off the geomagnetic equator has been re‐computed using the improved hydrogen distribution models which have become available since the earlier calculation by Liemohn. The Chamberlain model, with the input parameters determined by recent satellite observations, has been used to define the spatial distribution of the neutral hydrogen environment through which the ring current ions traverse. The resultant dependence of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…By analyzing the measured decay rates of the ions after geomagnetic storms and assuming two or more ions were present and that the decays were exponential in nature we were able to establish three separate lifetimes for the ions. By using the recently revised charge exchange decay lifetimes [Smith and Bewtra, 1978] and the dependence of these lifetimes on the mirror lati-tudes of these particles we determined for three geomagnetic storms the expected charge exchange lifetimes for H +, O +, and He + in the 6nefgy and L value range of the data. In this paper we showed the close agreement of the fitted decay lifetimes from the measurements to the charge exchange decay lifetimes to these three ions and inferred that H +, O +, and He + existed in the storm time ring currents we considered.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…By analyzing the measured decay rates of the ions after geomagnetic storms and assuming two or more ions were present and that the decays were exponential in nature we were able to establish three separate lifetimes for the ions. By using the recently revised charge exchange decay lifetimes [Smith and Bewtra, 1978] and the dependence of these lifetimes on the mirror lati-tudes of these particles we determined for three geomagnetic storms the expected charge exchange lifetimes for H +, O +, and He + in the 6nefgy and L value range of the data. In this paper we showed the close agreement of the fitted decay lifetimes from the measurements to the charge exchange decay lifetimes to these three ions and inferred that H +, O +, and He + existed in the storm time ring currents we considered.…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed that the off-90 ø pitch angle ion fluxes would not charge exchange decay as rapidly as was previously thought. In the review of the recent work associated with the determination of the charge exchange lifetimes for various ions in the• magnetosphere, Smith and Bewtra [1978] provide the updated and corrected lifetime values especially through the ring current region. While this area of space research has been experiencing some recent controversy over the various mechanisms, there is no question but that our understanding of the ring current source and loss mechanisms is progressing in a significant manner.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations